Determination of phthalic acid esters in water samples by hollow fiber liquid-phase microextraction prior to gas chromatography tandem mass spectrometry. (June 2018) - González-Sálamo, Javier; González-Curbelo, Miguel Ángel; Socas-Rodríguez, Bárbara; Hernández-Borges, Javier; Rodríguez-Delgado, Miguel Ángel
Abstract: A new hollow fiber liquid-phase microextraction (HF-LPME) method has been developed for the extraction of a group of phthalic acid esters (PAEs) of interest from different water samples prior to gas chromatography tandem mass spectrometry analysis. HF-LPME was carried out using 1-octanol as extraction solvent followed by a back extraction step with cyclohexane. The different parameters that affect HF-LPME such as sample pH, ionic strength, extraction time, stirring rate, extraction temperature and back extraction conditions were investigated. The optimized conditions involved the extraction of 10 mL of sample without pH adjustment or addition of salt during 75 min under a stirring of 850 rpm at 60 °C and subsequent desorption with 200 μL of cyclohexane for 10 min in an ultrasonic bath. The method was validated in terms of calibration and recovery studies using dibutyl phthalate-d4 as internal standard. The developed procedure gave satisfactory recovery (74–120%) and relative standard deviation values (<20%) for the studied PAEs in mineral, tap, pond and waste water samples. Highlights: A new HF-LPME-GC-MS/MS method was developed for the analysis of PAEs. Mineral, tap, pond and waste water samples were analyzed. Main parameters affecting the extraction efficiency were optimized. Recoveries ranged between 74 and 120% with RSD values below 20%. The developed method is simple, cheap and reliable.